Analisis Kasus Kehilangan Data Akibat Format dan Pemulihan Data Menggunakan Aplikasi Wondershare Recoverit - Purnama, Wahyu Aji; Servanda, Yustian; Djumhadi,; Wijayanto, Agus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Data loss is a prevalent issue encountered by computer users, often arising from accidental formatting of storage media. This study examines a specific instance of data loss on a flash disk due to accidental formatting and evaluates the efficacy of Wondershare Recoverit, a widely-used data recovery application. The research employs a case study approach, simulating a scenario in which a flash disk is inadvertently formatted, leading to data loss. The findings indicate that Wondershare Recoverit is an effective tool for recovering data lost due to formatting. The application features an intuitive and user-friendly interface, making it accessible to users with varying levels of technical expertise. Wondershare Recoverit can recover a wide range of file types, including photos, videos, documents, and other files lost due to formatting. Furthermore, the application supports data recovery from various storage devices, such as internal and external hard drives and other media
Keywords: Data Loss; Format; Flashdisk; Data Recovery; Wondershare Recoverit; Data Recovery Application